2017
DOI: 10.1007/s00294-017-0773-9
|View full text |Cite
|
Sign up to set email alerts
|

Mms1 is an assistant for regulating G-quadruplex DNA structures

Abstract: The preservation of genome stability is fundamental for every cell. Genomic integrity is constantly challenged. Among those challenges are also non-canonical nucleic acid structures. In recent years, scientists became aware of the impact of G-quadruplex (G4) structures on genome stability. It has been shown that folded G4-DNA structures cause changes in the cell, such as transcriptional up/down-regulation, replication stalling, or enhanced genome instability. Multiple helicases have been identified to regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…We show that Mms1 is not required to maintain CEB1 stability at both leading-and lagging-CEB1 revealing that G4 structures targeted by Mms1 are not deleterious for CEB1 stability. Our results are in good agreement with previous observations showing that Mms1 supports Pif1 function at G4 motifs only on the lagging strand [22,37], whereas Pif1 is not required for CEB1 stabilisation [33]. Here we show that RPA recruits Pif1 to CEB1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We show that Mms1 is not required to maintain CEB1 stability at both leading-and lagging-CEB1 revealing that G4 structures targeted by Mms1 are not deleterious for CEB1 stability. Our results are in good agreement with previous observations showing that Mms1 supports Pif1 function at G4 motifs only on the lagging strand [22,37], whereas Pif1 is not required for CEB1 stabilisation [33]. Here we show that RPA recruits Pif1 to CEB1.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, Pif1 could be directly recruited to G-rich motifs and G-quadruplex structures. Mms1 is a G4-DNA-binding protein that helps replication fork progression at G4 and Pif1 binding to specific G4 structures [22,37]. We show that Mms1 is not required to maintain CEB1 stability at both leading-and lagging-CEB1 revealing that G4 structures targeted by Mms1 are not deleterious for CEB1 stability.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Considering that G4-containing promoters corresponded principally to high transcriptional levels in a genome-wide study (Hänsel-Hertsch et al, 2016), induction of transcription may be the main role of G4s at gene promoters. In addition, since, except for helicases and few other proteins (Budhathoki et al, 2015;Butovskaya et al, 2019;Chen et al, 2018;David et al, 2019;Gueddouda et al, 2017;Paramasivam et al, 2009;Sauer and Paeschke, 2017;Scalabrin et al, 2017b;Voter et al, 2018;Wu et al, 2019), the vast majority of G4 binding protein stabilizes G4s (Brázda et al, 2014;Schwindt and Paeschke, 2018;Tosoni et al, 2015), recruitment of transcription factors by G4-interacting proteins may be the most common mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that ToPif-mediated G4-resolving activity in vivo is regulated by an unidentified protein factor. It was recently reported that the proteins Mgs1 and Mms1 in S. cerevisiae binding to G4 motifs in vivo partially depends on the helicase ScPif1 (41,42). Although ScPif1 is the major G4-unwinding helicase in cells, in the absence of Mgs1, the gross chromosomal rearrangement (GCR) rates in yeast is increased, similar to Pif1 deletion (41).…”
Section: Mutational Analysis Of the Residues Involved In G4 Binding And Unfoldingmentioning
confidence: 99%